2007
DOI: 10.1038/emm.2007.75
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry based proteomic analysis of human stem cells: a brief review

Abstract: Stem cells can give rise to various cell types and are capable of regenerating themselves over multiple cell divisions. Pluripotency and self-renewal potential of stem cells have drawn vast interest from different disciplines, with studies on the molecular properties of stem cells being one example. Current investigations on the molecular basis of stem cells pluripotency and self-renewal entail traditional techniques from chemistry and molecular biology. In this mini review, we discuss progress in stem cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…By this method they were able to discriminate membrane and membrane‐associated proteins from intracellular contaminants and identify additional markers during mouse ESC differentiation. In addition to methods aforementioned, numerous proteomic techniques have been developed and improved in recent years to suit specific stem cell research needs [60–63]. Many stem cell proteomic studies have been aimed at human stem cells either ESCs or ASCs [61,62].…”
Section: The Role For Proteomics In Stem Cell Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…By this method they were able to discriminate membrane and membrane‐associated proteins from intracellular contaminants and identify additional markers during mouse ESC differentiation. In addition to methods aforementioned, numerous proteomic techniques have been developed and improved in recent years to suit specific stem cell research needs [60–63]. Many stem cell proteomic studies have been aimed at human stem cells either ESCs or ASCs [61,62].…”
Section: The Role For Proteomics In Stem Cell Researchmentioning
confidence: 99%
“…In addition to methods aforementioned, numerous proteomic techniques have been developed and improved in recent years to suit specific stem cell research needs [60–63]. Many stem cell proteomic studies have been aimed at human stem cells either ESCs or ASCs [61,62]. They have followed several major directions, as described below, and they are depicted schematically in Fig.…”
Section: The Role For Proteomics In Stem Cell Researchmentioning
confidence: 99%
“…Mass spectroscopy (MS) based proteomics is becoming an efficient method characterized by systematic large-scale qualitative and quantitative mapping of the whole proteome of stem cell phenotypes from different niches, allowing for the rapid understanding the mechanisms that control their self-renewal ability, differentiation potential and regeneration capacity [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The proteome of potential hESCs has been compared to murine ESC (mESC) as well as hESC that were allowed to differentiate. Other stem cell proteomic signatures have also been published including hematopoietic stem cells (Spooncer et al, 2008; D'Alessandro et al, 2009), mESC (Ahn et al, 2008; Graumann et al, 2008; Gundry et al, 2008, 2010; Williamson et al, 2008; Intoh et al, 2009) and mensenchymal stem cells (Feldmann et al, 2005; Roche et al, 2006, 2009; Choi et al, 2007; Park et al, 2007; Kurpinski et al, 2009; Mareddy et al, 2009; Ji et al, 2010; Kim et al, 2010). In a further development on this theme there have been a number of studies that have compared the transcriptomic and proteomic expression levels identified in ESC and HSC during differentiation (Unwin and Whetton, 2006; Unwin et al, 2006; Spooncer et al, 2008; Williamson et al, 2008; Fathi et al, 2009).…”
Section: Regulation Of Protein Levels In Stem Cellsmentioning
confidence: 99%